Drying Shrinkage Strain of Palm-oil by-products Lightweight Concrete: A Comparison between Experimental and Prediction Models - Aslam, Muhammad; Shafigh, Payam; Jumaat, Mohd Zamin (Springer Verlag (Germany), 2018)
Drying shrinkage in concrete can be attributed to loss of moisture, variations in temperature, and the chemical reactions of cement with water and carbon dioxide, is one of the most important parameters which affects the durability and service life of the concrete structures. Recently, the lightweight concrete has got a considerable attention to be used in structural applications. Although, this concrete has very high drying shrinkage compared to conventional concrete. Therefore, the design engineers need an accurate and precise estimation of the concrete shrinkage, so that the safe and durable structure can be produced. The main objective of this research is to compare the development of drying shrinkage strain of three concrete mixes made of by-product aggregate namely oil pam shell and oil-palm-boiler clinker from the palm oil industry with the prediction models. For that purpose, ten (ACI209R, EN1992, MC2010, CEB/FIP1990, AASHTO-LRFD, GL2000, AS3600, JSCE, SAK and B3) prediction models of drying shrinkage have been selected from the standards, codes and researchers. All suggested parameters for the prediction models were considered in the estimation of shrinkage strain for the by-product concretes. In addition, the error percentage and coefficient of variation methods have been used to compute the accuracy of prediction models. The results showed that in early ages, almost all the prediction models estimated similar results with the experimental curves. However, at later ages, only few models for each concrete predicted similar results to the experimental values.